OPINI MAHASISWA UNTAG SURABAYA TERHADAP PERANAN FACEBOOK SEBAGAI MEDIA KOMUNIKASI SOSIAL - Putra, Pratama; Darmawan, Arif; Jupriono, Jupriono (Universitas 17 Agustus 1945 Surabaya, 2015)
The method used in this study is a qualitative research method of case studies. The case studiesfocus intensively on a particular object with a case study. Qualitative research aims to explain thephenomenon with deeply through data collection. The sampling technique in this research is the snowballtechnique ( snowball ). Through qualitative approach, data obtained from the field drawn conclusionsare specific to the general. Objects in the study were students of University August 17 Fisip Surabaya arestill active are 25 people. Observations made during the first month . Data collection techniques used inthis research is through field research and library research. And data analysis techniques used in thisresearch through data reduction, data display, draw conclusions and verification. The results showedthat the site facebook is a social media platforms are quite good and efficient. Very good role in socialkomuniikasi ie as source of information about friends , communities, groups and data sharing. Then interms of the economic benefits are not good enough but still no progress. facebook but as acommunication medium between friends can also as a medium to promote businesses . in education isquite minimal benefits from the data that the author did little is agreed that education has an importantrole in facebook. then from the social and cultural , social development is significant but the impact thatcaused the not too big for our culture.Keywords: opinion, students, social communications, facebook.